Where will I live? - McCarney, Rosemary A (Second Story Press, 2017)
"This stunning photo-based picture book for younger readers takes a look at the thousands of children around the world who have been forced to flee war, terror, hunger, sickness, and natural disasters - young refugees on the move with very little left except questions. It's hard to imagine, but the images here will help unaffected children understand not only what this must feel like, but also how very lucky they are. The final message is that children, even with uncertain futures, are resilient and can face uncertainty with optimism. Gripping images are from the United Nations High Commissioner for Refugees and include photographs of children in countries including Lebanon, Rwanda, Iraq, Niger, Hungary, Jordan, and Greece, among others."--